Principles of accounting in the Duchy of Warsaw – problems with cash accounts - MAŁGORZATA GARSTKA (Zeszyty Teoretyczne Rachunkowości)
Purpose: The aim of the article is to present the accounting principles used in the Duchy of Warsaw (1807–1815) and to provide arguments that support these principles.Methodology/approach: The methodology involves analyzing historical sources, con-ducting a literature review organized by substantive issues related to the system of the Principality, and analyzing thematic and chronological arrangements of information obtained from the Central Archives of Historical Records.Findings: When settling accounting irregularities in the Duchy of Warsaw during the takeover of accounts from Prussian officials, the following accounting criteria and principles, including ethics, were applied: reconciliation of closing and opening states, correctness of accounting documents, maintaining clean entries when correcting errors, prioritizing content over form, materiality considerations, internal control measures, responsibility, professional competency requirements, and proper organization within accounting practices.Practical implications: The article will make accountants aware of the historical basis of certain principles used today and highlight the importance attached to them in times when keeping accounts was organizationally difficult. This can reinforce current accountants’ respect for these principles and reinforce their importance and need to be followed.Originality/value: The article provides valuable insights into historical documents from the Duchy of Warsaw. It shows what rules were used and whether they were the same as today while highlighting problems with compliance.